HALAL TOURISM DEVELOPMENT STRATEGY ON COMMUNITY ECONOMIC DEVELOPMENT IN MATANG RAYEUK VILLAGE, IDI TIMUR DISTRICT AND LEUGE VILLAGE, PEREULAK DISTRICT, WEST ACEH REGENCY - Daniel Amsal; Azhari Akmal Tarigan; Maryam Batubara (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The development of halal tourism is one solution to the development of the community's economy and the development of remote villages because most of the distribution of objects and tourist attractions are in the village area. In Gampong Matang Rayeuk PP, Idi Timur District and Gampong Leuge, Peureulak District, East Aceh Regency, they are currently developing halal tourism for the economic development of the community. This study aims to analyze: (1) the strategy of developing halal tourism on the economic development of the community in Matang Rayeuk PP Village, East Idi District and Leuge Village, Peureulak District, East Aceh Regency. (2), community participation in the development of halal tourism on the economic development of the community in Matang Rayeuk Village, East Idi Subdistrict and Leuge Village, Peureulak District, East Aceh Regency (3), implications of halal tourism development on the economic development of the community in Matang Rayeuk Village, PP, Idi Subdistrict. East and Leuge Village, Peureulak District, East Aceh Regency. In this study, researchers used the constructivist paradigm. In accordance with the paradigm and problems chosen in this study, this study uses a qualitative approach. The data analysis technique in this study uses the Miles and Huberman interactive model. The results of the study show that: (1) Halal tourism development strategies for the economic development of the community (2) Community participation are: Tour managers, tour guides, producers of various creative products, traders and members of art groups. (3) Implications for the economy of Gampong Matang Rayeuk PP, Idi Timur District and Gampong Leuge, Peureulak District, East Aceh Regency